1989
DOI: 10.1056/nejm198906153202402
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Recombinant Human Granulocyte Colony-Stimulating Factor on Neutropenia in Patients with Congenital Agranulocytosis

Abstract: Congenital agranulocytosis is a disorder characterized by severe neutropenia and a profound deficiency of identifiable neutrophil progenitors in bone marrow. In an attempt to stimulate neutrophil production and thereby reduce the morbidity and mortality associated with this disease, we administered recombinant human granulocyte colony-stimulating factor (rhG-CSF) in doses of 3 to 60 micrograms per kilogram of body weight per day to five patients with congenital agranulocytosis. In all five patients, an increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
148
0
9

Year Published

1990
1990
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 453 publications
(166 citation statements)
references
References 34 publications
5
148
0
9
Order By: Relevance
“…Cord blood: linear associations potential use of exogenous G-CSF or GM-CSF in the management of neonatal sepsis. Experience with the use of these factors in children and adults has indicated that G-CSF is well tolerated, is associated with few side effects, and can produce an improvement in neutrophil counts and a reduction in the number and severity of infections (8,(48)(49)(50)(51)(52). In contrast.…”
Section: Discussionmentioning
confidence: 99%
“…Cord blood: linear associations potential use of exogenous G-CSF or GM-CSF in the management of neonatal sepsis. Experience with the use of these factors in children and adults has indicated that G-CSF is well tolerated, is associated with few side effects, and can produce an improvement in neutrophil counts and a reduction in the number and severity of infections (8,(48)(49)(50)(51)(52). In contrast.…”
Section: Discussionmentioning
confidence: 99%
“…The use of G-CSF therapy has radically changed patient outcomes. 26 HSCT is still the only curative treatment for patients refractory to G-CSF and in cases of clonal evolution (AML and MDS).…”
Section: Specific Considerations Regarding Ibmfs With Single-cell Defmentioning
confidence: 99%
“…1,2 Recombinant human granulocyte colony-stimulating factor (rh-G-CSF) has revolutionized the care of individuals with CN; it acts by stimulating neutrophil production and thereby reduces the incidence and severity of infections. 3,4 Data from the International Registry for Severe Chronic Neutropenia (SCNIR) revealed that CN is a preleukemic disorder, with an estimated 15% risk of transformation to myelodysplastic syndrome (MDS) and acute leukemia. 5 While most CN patients have developed MDS or acute myeloid leukemia (AML) in the context of prior rh-G-CSF treatment, few cases of AML were described in the pre-G-CSF era.…”
Section: Introductionmentioning
confidence: 99%